The study on the liquidity trap in China's money market - Caroline Geetha; Soon, Lin Fei (Universiti Malaysia Sabah, 2020)
This study aims to identify the liquidity trap and indicate the factors that affect money liquidity in China. A liquidity trap is an economical issue which is faced by lots of developed countries when their economy has achieved a certain stage of development, such as Japan, America and Europe. However, China as the fastest-growing developing country, some scholars suggested that its economy has also being trapped in a liquidity trap. Thus, to verify this opinion, monthly data of several important economic indexes were selected through a series of econometric process to indicate two major findings. First, the economy of China has not fallen into a liquidity trap. Besides, the interest rate and real estate price had a negative impact on the liquidity of money in China while the development of the financial industry had a positive contribution.